PENINGKATAN KINERJA PEMASARAN BERBASIS MARKETING RELATION DAN POSITIONING - Andi Ahmad A (Jurnal Riset Bisnis Indonesia, 2014)
The purposes of this study are to describe and analyze: 1) the effect of marketing relation onthe Positioning, 2) the effect of marketing relation on marketing performance, and 3) the effect ofpositioning on marketing performance. The population in this study is outlet agent of PT. Coca -Cola as a distributor of Coca- Cola products in the area of West Java, part of Tambun, Cibitung,and Cikarawang. The sample consists of 54 people who were selected using non-probabilitymethod, that is purposive sampling method. The data in this research is primary data obtained fromquestionnaires distributed to respondents. Data were analyzed using Partial Least Square (PLS).Based on the results of research and discussion, it can be drawn a few conclusions, such as 1)there is a positive significant influence of marketing relation on positioning, 2) there is no significantinfluence of marketing relation on performance marketing, and 3) there is a positive and significantinfluence of the positioning on performance marketing.Keywords: Marketing Relation, Positioning, Marketing Performance.